Perceived Challenges of National Education Policy, 2020 by the Students (Indian Journal of Extension Education, 2022)
National Education Policy, 2020 is a progressive shift towards a more scientific approach to education and if it is enforced in its true vision, the new education structure can bring India stood up with the leading countries in the world. It is aiming to develop creative potential, skills, and analytical thinking which will be the need in the global job market. The policy has challenges for the students and the teachers. The present study focused on the perception of college students in India about NEP, 2020 concerning challenges like overburden of syllabus, lack of infrastructure, and transportation facilities, focus on regional languages, Disparity between rural and urban areas in manpower and quality of education. The results of the study indicated that out of 120 respondents, 45(37.50%) respondents agreed, for the statement “Overburden of syllabus”, followed by “Universal access to education” were agreed by around half of the respondents i.e. 64(53.33%), and 11(09.16%) were disagreed.